SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN LAHAN PERTANIAN YANG TEPAT UNTUK MENINGKATKAN HASIL PANEN CABAI MENGGUNAKAN METODE MOORA - suci ramadani; HUSNUL KHAIR; SRI DEVI BANGUN (STMIK KAPUTAMA, 2020)
Decision support system is a system that can solve problems that occur in ranking quickly and can find out the highest to lowest value in a selection. In this paper is one of the case studies that can be solved using a decision support system, where the problem faced in the selection of agricultural land is how to choose the best chili and to make a selection must use manually and the assessment process takes a long time. to get results. Therefore created a problem how to determine an appropriate agricultural land selection problem to determine the good chili crop yield using the MOORA method and where the MOORA method is used to test in correctness that aims to determine the accuracy of the value obtained by the system, the results of the best land selection is in the city area of binjai jln sawi payaroba west binjai, plus the value of the weight of the criterion and the modification trial which aims to find out how many criteria can be added.